The Melanin-Concentrating Hormone (MCH) System Modulates Behaviors Associated with Psychiatric Disorders - Chung, Shinjae; Verheij, Michel M. M.; Hesseling, Peter; van Vugt, Ruben W. M.; Buell, Mahalah; Belluzzi, James D.; Geyer, Mark A.; Martens, Gerard J. M.; Civelli, Olivier (PLOS ONE, 2011)
Deficits in sensorimotor gating measured by prepulse inhibition (PPI) of the startle have been known as characteristics of patients with schizophrenia and related neuropsychiatric disorders. PPI disruption is thought to rely on the activity of the mesocorticolimbic dopaminergic system and is inhibited by most antipsychotic drugs. These drugs however act also at the nigrostriatal dopaminergic pathway and exert adverse locomotor responses. Finding a way to inhibit the mesocorticolimbic- without affecting the nigrostriatal-dopaminergic pathway may thus be beneficial to antipsychotic therapies. The melanin-concentrating hormone (MCH) system has been shown to modulate dopamine-related responses. Its receptor (MCH1R) is expressed at high levels in the mesocorticolimbic and not in the nigrostriatal dopaminergic pathways. Interestingly a genomic linkage study revealed significant associations between schizophrenia and markers located in the MCH1R gene locus. We hypothesize that the MCH system can selectively modulate the behavior associated with the mesocorticolimbic dopamine pathway. Using mice, we found that central administration of MCH potentiates apomorphine-induced PPI deficits. Using congenic rat lines that differ in their responses to PPI, we found that the rats that are susceptible to apomorphine (APO-SUS rats) and exhibit PPI deficits display higher MCH mRNA expression in the lateral hypothalamic region and that blocking the MCH system reverses their PPI deficits. On the other hand, in mice and rats, activation or inactivation of the MCH system does not affect stereotyped behaviors, dopamine-related responses that depend on the activity of the nigrostriatal pathway. Furthermore MCH does not affect dizocilpine-induced PPI deficit, a glutamate related response. Thus, our data present the MCH system as a regulator of sensorimotor gating, and provide a new rationale to understand the etiologies of schizophrenia and related psychiatric disorders.